Platelet adhesiveness in young patients with ischaemic stroke. - Sharma, S C (1977)
A significant increase in platelet adhesiveness was observed in 13 patients who developed ischaemic stroke at high altitude and in 43 patients who developed stroke at low altitude when compared with a similar group of normal healthy volunteers. Eighty-eight percent of the patients were below the age of 40 years. The role of platelet adhesiveness in the pathogenesis of cerebral schaemia in young patients is discussed.